Assessing the effectiveness of health care cost containment measures - Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2011)
Using SOEP panel data and difference-in-differences methods, this study is the first to empirically evaluate the effectiveness of four different health care cost containment measures within an integrated framework. The four measures investigated were introduced in Germany in 1997 to reduce moral hazard and public health expenditures in the market for convalescent care. Doubling the daily copayments was clearly the most effective cost containment measure, resulting in a reduction in demand of about 20 percent. Indirect measures such as allowing employers to cut statutory sick pay or paid vacation during health spa stays did not significantly reduce demand.
urn:nbn:de:101:1-201104134390
Keywords: H51; I11; I18; J22; 330; health expenditures; cost containment measures; copayment; convalescent care; SOEP; Gesundheitskosten; Selbstbeteiligung; Heilbad; Rehabilitation; Wirkungsanalyse; Schätzung; Deutschland